2000
DOI: 10.1002/(sici)1097-4636(20000615)50:4<465::aid-jbm1>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Patterned poly(chlorotrifluoroethylene) guides primary nerve cell adhesion and neurite outgrowth

Abstract: A thesis submitted in confonity mth the requirements for the degree of Masten of Applied Science. Graduate Department of Chemical Engineering and Applied Chemistry lnstitute of Biomaterials and Biomedical Engineering in the University of Toronto @Copyright by Samar Saneinejad (1 999) National Library 1+1 , , n a , Bibliothèque nationale du Canada Acquisitions and Acquisitions et Bibliog raphic Services services bibiiographiques 395 Wellington Street 395. nie Wsllirrgton OttawaON K1AON4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several groups have found that peptide-modified surfaces enhance cell adhesion [86][87][88][89] . In vitro, YIGSR, IKVAV and RGD enhanced the interaction of primary neuronal cells with fluoropolymers 90,91 and directed neuron adhesion and outgrowth 92 .…”
Section: Biomaterials Considerationsmentioning
confidence: 93%
“…Several groups have found that peptide-modified surfaces enhance cell adhesion [86][87][88][89] . In vitro, YIGSR, IKVAV and RGD enhanced the interaction of primary neuronal cells with fluoropolymers 90,91 and directed neuron adhesion and outgrowth 92 .…”
Section: Biomaterials Considerationsmentioning
confidence: 93%